2006
DOI: 10.1111/j.1440-1746.2006.04444.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with gallstone and biliary sludge formation during pregnancy

Abstract: Decrease in GBEF is the most significant risk factor for newly developed gallstone and sludge in pregnant women, while multiple childbirths is the other but less important risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 34 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…There are several reports from Turkey on the etiological factors of gallstone formation. Pregnancy (12), iron deficiency anemia (13) and bacterial infections such as H. pylori were suggested to have possible roles in the formation of gallstones (14). Okumuçoglu et al (15) reported in their series that cholesterol stones are almost three times as frequent as other types of stones and concluded that this might be related to the dietary habits of Turkish people.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports from Turkey on the etiological factors of gallstone formation. Pregnancy (12), iron deficiency anemia (13) and bacterial infections such as H. pylori were suggested to have possible roles in the formation of gallstones (14). Okumuçoglu et al (15) reported in their series that cholesterol stones are almost three times as frequent as other types of stones and concluded that this might be related to the dietary habits of Turkish people.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports from Turkey on the etiological factors of gallstone formation. Pregnancy (12), iron deficiency anemia (13) and bacterial infections such as H. pylori were suggested to have possible roles in the formation of gallstones (14). okumuşoğlu et al (15) reported in their series that cholesterol stones are almost three times as frequent as other types of stones and concluded that this might be related to the dietary habits of Turkish people.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the combination of pregnancy and fascioliasis may have increased the risk of developing stones in this patient. [6][7][8] The risk of gall bladder stones increases in pregnancy, especially in the last two trimesters, because of the alteration in biliary lipid composition and gall bladder hypomotility by sex steroids. 6 Fascioliasis, on the other hand, causes inflammation and hyperplasia of the epithelium, leading to gall bladder edema and mechanical obstruction.…”
Section: Commentmentioning
confidence: 99%
“…[6][7][8] The risk of gall bladder stones increases in pregnancy, especially in the last two trimesters, because of the alteration in biliary lipid composition and gall bladder hypomotility by sex steroids. 6 Fascioliasis, on the other hand, causes inflammation and hyperplasia of the epithelium, leading to gall bladder edema and mechanical obstruction. 7,8 These changes ultimately will cause bile stasis and subsequent development of bile stones.…”
Section: Commentmentioning
confidence: 99%